The European Arrest Warrant in Advancing Legal Integration: A Comparative Study of Kosovo and Bosnia and Herzegovina - Daci, Greta (Acta Universitatis Danubius. Juridica, 2025)
Transnational crime presents a significant challenge to the sovereignty of the European countries as well as the Western Balkans. The challenges of traditional extradition have emphasized the need for prevention mechanisms and alternative cooperation methods within Europe. The European Arrest Warrant (EAW), established through reciprocal recognition, has simplified extradition and expanded its influence beyond the EU to the Western Balkans. These countries, pursuing European integration, face increasing organized crime that directly affects Europe. This research investigates the influence and implications of the EAW on the Balkans, concentrating on the harmonization of non-EU countries with EAW principles within the normative framework. Through a comparative study of Kosovo and Bosnia and Herzegovina, the paper analyses their legal, instrumental, and political frameworks, assessing extradition implementation and policy alignment. Both countries exhibit partial legal harmonization with EU standards. The study concludes that, despite not being part of the EAW, the political structures of these states help externalize EAW norms into the Western Balkans. Using qualitative comparative legal methodology, the findings contribute to scholarship on legal harmonization, European law, transnational criminal law, and inform policymakers on regional security cooperation.